Implementasi Kelayakan Radio Wireless PTP 5.8 GHz pada Area Terpisah - Ahmad Lutfi Ramadhan; Supriadi Supriadi; Hari Purwadi (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
This study aims to evaluate the feasibility of implementing a 5.8 GHz point-to-point (PTP) wireless radio system as a network connectivity solution for geographically separated areas. The main issue addressed is the limitation of cable-based infrastructure in hard-to-reach locations, along with the need for a stable, efficient, and cost-effective network. The research employed an experimental approach, including link planning, radio device installation, Line of Sight (LoS) testing, and network performance measurement. Data were collected through direct field testing by measuring throughput, latency, packet loss, and received signal strength indicator (RSSI) values. The results show that the 5.8 GHz PTP radio implementation is capable of providing stable connectivity with average throughput sufficient for data access needs, low latency, and packet loss within acceptable network tolerance standards. The main factors affecting connection quality include LoS conditions, frequency interference levels, and antenna alignment accuracy. Based on the analysis, the 5.8 GHz wireless PTP system is considered feasible as an alternative network infrastructure for separated areas with relatively lower costs compared to conventional cable installations. In conclusion, this technology is both effective and efficient in supporting network expansion, particularly in regions with geographical barriers or limited physical infrastructure